ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA KOPERASI KREDIT SEWILAYAH PUSKODIT SWADAYA UTAMA TAHUN 2015-2017 - Herdi, Henrikus; Desy Apryanti Site, Maria (Accounting UNIPA - Jurnal Akuntansi, 2022)
aProblems that often occur in a credit union are usually caused by financial problems. To measure the level of financial health of a credit union, it can be used financial ratio analysis using the Altman Z- Score model. This study aims to predict bankruptcy in credit unions under Puskopdit Swadaya Utama area using the Altman Z-Score model. The sample in this study was credit unions under Puskopdit Swadaya Utama area in 2015-2017 consisting of 16 credit unions. The data sources used were secondary data in the form of credit union financial statements. The analysis technique used is the Altman Z-Score bankruptcy prediction model. The results show that there are credit unions that are included in healthy category during 2015- 2017, namely Obor Mas, Tuke Jung, Ortal, Ladang, Bintang Timur and Serba Te credit unions. In 2015 and 2016, Kelubagolit credit union is in the gray area category, but in 2017 the credit union is in the healthy category. In addition, there are credit unions that in 2015-2017 are included in the gray area category, namely Sube Huter, Tuke Ler, Hiro Heling, Bina Pertiwi, and Surya Sakti credit unions. San Dominggo credit union in 2015 and 2016 is in the category of bankruptcy, but in the following year it is included in the gray area category. The credit unions include in the bankrupt category from 2015-2017 are Remaja Hokeng and Ankara credit unions. In 2015, Plelu Meluk credit union is included in the gray area category, the performance of this credit union continus to decline and in 2016 and 2017 the credit union is in the bankrupt category. And in 2018, Remaja Hokeng Youth experiences an amalgamation with the Mitan Gitan credit union. This shows that the level of accuracy of the Altman Z-Score model ishigh.